2014
DOI: 10.1017/s2045796014000407
|View full text |Cite|
|
Sign up to set email alerts
|

Developing a change model for peer worker interventions in mental health services: a qualitative research study

Abstract: An empirically and theoretically grounded change model can be articulated that usefully informs the development, evaluation and planning of peer worker interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 47 publications
(51 reference statements)
8
142
0
5
Order By: Relevance
“…In the next stage 'constant comparison' techniques were borrowed from Grounded Theory (Strauss and Corbin 1998) to develop cross-cutting themes that moved the analysis to a more explanatory level (Mason 2002). A set of themes emerged around the mechanisms of peer support, and this analysis has been reported elsewhere (Gillard et al 2014b). A further set of themes emerged that offered insight into how issues of risk management and crisis were related to the peer worker role; it is this analysis that is reported here.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the next stage 'constant comparison' techniques were borrowed from Grounded Theory (Strauss and Corbin 1998) to develop cross-cutting themes that moved the analysis to a more explanatory level (Mason 2002). A set of themes emerged around the mechanisms of peer support, and this analysis has been reported elsewhere (Gillard et al 2014b). A further set of themes emerged that offered insight into how issues of risk management and crisis were related to the peer worker role; it is this analysis that is reported here.…”
Section: Discussionmentioning
confidence: 81%
“…Elsewhere we have reported findings suggested that building relationships based on shared lived experiencein order to both role model recovery and to act as a bridge to mental health services-is a core mechanism underlying the peer worker role (Gillard et al 2014b). As such the need to provide specific training and support to address those challenges would seem imperative.…”
Section: Discussionmentioning
confidence: 98%
“…The peer worker embodies (Kontos and Naglie ) therapeutic change as they enact the PW role – the recovered, productive self (Gillard et al . ) – while a sense of alignment between peer worker and supported person imbues their relationship with therapeutic potential in three important ways. First, there is the sense of connection (that lies at the heart of all therapeutic relationships) between PW and supported person, made real in the shared experiential knowledge of having ‘been there’ (or somewhere similar) at some point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, such as Solomon (7), have described mechanisms thought to yield benefits for those who receive peer specialist services (for example, use of experiential learning and natural social support and mutual benefit of peer specialist work). Others, such as Gillard et al (8), have used qualitative approaches to suggest effective mechanisms (for example, develop trusting relationships, use role modeling to build hope, challenge stigma, build skills, and promote engagement in mental health services and community supports). Although these mechanisms and theories have face validity, studies have not been done to prospectively assess their explanatory power.…”
Section: Peer Specialists’ Roles Settings and Theoretical Orientationsmentioning
confidence: 99%